Efeito da adição de ureia e do tempo de fermentação sobre as características da silagem de sorgo (Sorghum vulgare) - Gomide, J A; Assis, F N; Nascimento Jr., D (Revista Ceres, 2025)
This experiment dealt with the effects of urea addition (0.53) on some changes taking place in sorghum silages during its early stages of fermentation. Samples of the sorghum plant as well as its silage after 1, 3, 7, 14, 28 and 63 days of storage in concrete experimental silos (1,0 x 0,40 m) were analysed.